Recession and recovery in the OECD. - Chamberlin, G; Yueh, L (Palgrave Macmillan, 2009)
During the last year the global economy has experienced its most severe recession since the Great Depression. This article compares the UK experience with that of OECD member countries- a group of the major industrialised economies. While important economies such as Japan and Germany saw a larger fall in output, the depth of the UK recession was larger than the OECD average. Recent data shows the global economy beginning to emerge from recession, but the projections are for a weak and fragile recovery as households, businesses and governments continue to pay off debts and rebuild their balance sheets. In fact, the major economies could be susceptible to a further downturn resulting in a double-dip recession. The second part of this article looks at the factors underlying recent growth forecasts made by the OECD and the IMF.